Three-dimensional particle electrode system treatment of organic wastewater: A general review based on patents. (25th July 2021) - Li, Hongtao; Yang, Haitao; Cheng, Jiaxin; Hu, Chaoquan; Yang, Zekun; Wu, Congcong
Abstract: Three-dimensional (3D) electrocatalytic oxidation technology is an effective organic wastewater treatment method. Given the strong demand for environmental protection and the universality of 3D electrode degradation of pollutants, this field has great development prospects, and a large number of research results have been published in recent years. In this paper, several studies on patents in the field of 3D electrolytic treatment of organic wastewater were discussed to conduct a comprehensive review and analysis of this field from the perspective of patents. The structures of the reactor, the electrode plate material, the particle electrode, the catalyst, the main process parameters (initial pH, aeration, electrode spacing, particle electrode filling amount, particle electrode size, electrolyte, and electrolysis time), and energy consumption were presented. The effects of process parameters, power supply, current, and voltage on degradation efficiency were also discussed. The research status of the reactor and electrode materials was mainly explored, and the current problems and related development suggestions for 3D electrocatalytic oxidation of organic wastewater were elucidated. Graphical abstract: Image 1 Highlights: The three-dimensional particle electrode system based on patents were reviewed. The basic theory of 3D electrocatalytic oxidation were introduced. The electrode materials and reactors of 3D particle electrode system were listed. Characteristics of the main process parameters using in practice were discussed. The existing problem was presented and possible outlook was suggested.